How repeats rearrange chromosomes: The molecular basis of chromosomal inversions in deer mice - Landen Gozashti; Olivia S. Harringmeyer; Hopi E. Hoekstra (Cell Reports)
Summary: Large genomic rearrangements, such as chromosomal inversions, can play a key role in evolution, but the mechanisms by which these rearrangements arise remain poorly understood. To study the origins of inversions, we generated chromosome-level de novo genome assemblies for four subspecies of the deer mouse (Peromyscus maniculatus) with known inversion polymorphisms. We identified ∼8,000 inversions, including 47 megabase-scale inversions, that together affect ∼30% of the genome. Analysis of inversion breakpoints suggests that while most small (<1 Mb) inversions arose via ectopic recombination between retrotransposons, large (>1 Mb) inversions are primarily associated with segmental duplications (SDs). Large inversion breakpoints frequently occur near centromeres, which may be explained by an accumulation of retrotransposons in pericentromeric regions driving SDs. Additionally, multiple large inversions likely arose from ectopic recombination between near-identical centromeric satellite arrays located megabases apart, suggesting that centromeric repeats may also facilitate inversions. Together, our results illuminate how repeats give rise to massive shifts in chromosome architecture.